Immunologic Response to Tumor Ablation with Irreversible Electroporation - Li, Xiaoxiang; Xu, Kui; Li, Wei; Qiu, Xiuchun; Ma, Baoan; Fan, Qingyu; Li, Zhao (PLOS ONE, 2012)
Background Irreversible electroporation (IRE) is a promising technique for the focal treatment of pathologic tissues, which involves placing minimally invasive electrodes within the targeted region. However, the knowledge about the therapeutic efficacy and immune reactions in response to IRE remains in its infancy. Methods In this work, to detect whether tumor ablation with IRE could trigger the immunologic response, we developed an osteosarcoma rat model and applied IRE directly to ablate the tumor. In the experiment, 118 SD rats were randomized into 4 groups: the control, sham operation, surgical resection, and IRE groups. Another 28 rats without tumor cell implantation served as the normal non-tumor-bearing group. We analyzed the changes in T lymphocyte subsets, sIL-2R and IL-10 levels in the peripheral blood one day before operation, as well as at 1, 3, 7,14 and 21 days after the operation. Moreover, splenocytes were assayed for IFN-γ and IL-4 production using intracellular cytokine staining one day before the operation, as well as at 7 and 21 days after operation. Results We found that direct IRE completely ablated the tumor cells. A significant increase in peripheral lymphocytes, especially CD3+ and CD4+ cells, as well as an increased ratio of CD4+/CD8+ were detectable 7 days after operation in both the IRE and surgical resection groups. Compared with the surgical resection group, the IRE group exhibited a stronger cellular immune response. The sIL-2R level of the peripheral blood in the IRE group decreased with time and was significantly different from that in the surgical resection group. Moreover, ablation with IRE significantly increased the percentage of IFN-γ-positive splenocytes. Conclusion These findings indicated that IRE could not only locally destroy the tumor but also change the status of cellular immunity in osteosarcoma-bearing rats. This provides experimental evidence for the clinical application of IRE in osteosarcoma treatment.